Resilience as a rection mechanism to face forced displacement in three women, victims of the armed conflict (Encuentros, 2024)
The objective of the following research was to identify the presence of resilience as a reaction mechanism to face forced displacement in three women, victims of the armed conflict in Colombia. For the analysis of the information, a qualitative methodology was used. The data collection was carried out through in-depth interviews, to get to know the ways in which three women, victims of forced displacement, faced this situation. The obtained testimonies brought to light the abilities that some people in conditions of displacement gain and use to overcome their circumstances of arrival to a new place, starting with accepting family ruptures, facing previously unlived work situations, finding the ways to start over and develop new skills that empower them in their new social environment. That means dedicating themselves to start life projects that allow them to overcome their now precarious living conditions. It was identified that the projects that were developed by them, even though they were related to their survival, they also go beyond and allow a glimpse to both their will to overcome the situation and the confidence in their own abilities.
Keywords: Resilience, reaction, armed conflict, political violence, forced displacement.